RUNX2-modifying enzymes: therapeutic targets for bone diseases - Kim, Woo-Jin; Shin, Hye-Lim; Kim, Bong-Soo; Kim, Hyun-Jung; Ryoo, Hyun-Mo (Experimental & molecular medicine, 2020)
RUNX2 is a master transcription factor of osteoblast differentiation. RUNX2 expression in the bone and osteogenic front of a suture is crucial for cranial suture closure and membranous bone morphogenesis. In this manner, the regulation of RUNX2 is precisely controlled by multiple posttranslational modifications (PTMs) mediated by the stepwise recruitment of multiple enzymes. Genetic defects in RUNX2 itself or in its PTM regulatory pathways result in craniofacial malformations. Haploinsufficiency in RUNX2 causes cleidocranial dysplasia (CCD), which is characterized by open fontanelle and hypoplastic clavicles. In contrast, gain-of-function mutations in FGFRs, which are known upstream stimulating signals of RUNX2 activity, cause craniosynostosis (CS) characterized by premature suture obliteration. The identification of these PTM cascades could suggest suitable drug targets for RUNX2 regulation. In this review, we will focus on the mechanism of RUNX2 regulation mediated by PTMs, such as phosphorylation, prolyl isomerization, acetylation, and ubiquitination, and we will summarize the therapeutics associated with each PTM enzyme for the treatment of congenital cranial suture anomalies. Regenerative medicine: Manipulating modifications that control bone-building Therapies that modulate the activity of the regulatory protein RUNX2 could potentially restore normal bone development in a range of skeletal disorders, and repair damage from injury or degeneration. RUNX2 is an essential regulator of genes that drive formation of bone-producing osteoblast cells. It can be activated or inactivated by the enzymatic addition of various chemical groups. Hyun-Mo Ryoo and colleagues at Seoul National University, South Korea, review the role of such modifications in bone disorders. For example, the loss of modifications activated by RUNX2 can result in delayed integration of the bones that form the skull. The authors highlight potential opportunities to manipulate these modification processes to treat this and other developmental disorders. Similar strategies could also promote repair of fractures or counter osteoporotic bone loss.